The Role of the Riau Province National Unity and Political Agency in Political Education to Increase Voter Participation in the 2024 General Election - Syafhendry; Rizky Setiawan S; Khotami; Rozand Awaramsyah Rachman; Asri Karly (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
In order to make general elections and regional head elections in Indonesia a success, the role of all stakeholders is needed. The democratic festival, which is held every five years in Indonesia, is very crucial for the development and progress of the Indonesian nation. In this research, the author focuses on the role of the national and political unitary body of Riau Province in carrying out its authority in the political field related to political education for the voting public. Political education is to increase people's knowledge so that they can participate optimally in the political system. Based on 2019 Election data, Riau Province is ranked 10th in the Permanent Voter List with 3,863,197 voters, while the largest number of voters is in West Java Province. From the Provisional Voter List data, there was an increase of one million voters in Riau Province, namely 4,740,392 voters. The importance of political education for the community is to provide information and education related to General Elections and Regional Head Elections, increase voter participation and make voters smart in voting. The aim of this research is to see the role of the Riau Province National Unity and Politics Service in educating voters and find out the inhibiting factors in implementing the authority of the Riau Province National Unity and Politics Service. The method and type of this research is Qualitative Descriptive. The technique for attracting informants uses a proportional sampling technique and data collection techniques in this research are interviews, observation, literature study and documentation. The benefits of this research are as reference material both for the development of knowledge in the field of politics and for government administrators in increasing participation for the voting public and educating voters.